Designing Insya' teaching material for the second-grade students at the Khadimul Ummah Islamic Boarding School in Bintan - Suja, Aidillah; Haq, Muhammad A'inul; Yasmar, Renti; Ridho, Ali; Sofian, Ganjar Yusup (MAN 4 Kota Pekanbaru, 2023)
This study aims to design teaching materials for Insya' subjects and explain the design process and its outcomes. The research method used was Design-Based Research (DBR), which belongs to Research and Development (R&D) and consists of four stages: problem identification and analysis, solution design, iterative testing cycles, and final reflection. The data were collected through questionnaires and interviews with both quantitative and qualitative analysis applied. The results show two main findings: first, the teaching materials design goes through three stages, namely setting objectives, setting materials, and formulating evaluations. Second, the outcomes that have been designed were stated to be 'good' category.